Risk, Resource, Redemption? The Parenting and Custodial Experiences of Young Offender Fathers. Issue 1 (26th October 2015) - Ladlow, Linzi; Neale, Bren
Abstract : Drawing on an ESRC funded qualitative longitudinal study of young fatherhood, this article explores the experiences of young offender fathers, the complex intersection of offender and fatherhood pathways for young men and the impact of professional support and tailored intervention programmes on these processes. The article challenges the axiom of young offender fathers as inherently 'risky', and suggests the utility of a dynamic, life course approach to criminal policy and practice that recognises the fluidity of their life journeys, and brings ideas of redemption more centrally into the picture.